Towards heterogeneous faith communities : understanding transitional processes in Seventh-day Adventist Churches in South Africa - Parker, Alan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (DTh (Practical Theology and Missiology))--University of Stellenbosch, 2004.